Student’s Attitude and Perception with the Use of Technology in the University - Orgaz, Francisco (2018)
This study aims to know the relationship between the variables attitude toward social networks, attitude toward technology, perception about technology and use of technology by university students. The methodology used has been a questionnaire, which has been applied to students of the Technological University of Santiago (UTESA) of the Dominican Republic. The data has been analyzed through the statistical programs SPSS and SmartPLS (Partial Least Square technique -PLS-). Among the main results, it has been found that students ‘attitude toward technology influences their perception about technology, and that students’ attitude toward social networks has a positive influence on the use of technology.